Brief Report: A Latent Class Analysis of Guideline Compliance Across Nine Health Behaviors - Pettigrew, Simone; Dana, Liyuwork; McAleese, A.; Bastable, A.; Drane, Cathy; Sapountsis, Nina (2021)
Background: Prevalence figures for health-related behaviors disguise the existence of behavioral clusters. A growing body of work indicates the potential effectiveness of using simultaneous (versus sequential) approaches to targeting health-related behaviors to make deeper inroads into addressing non-communicable diseases. To inform future interventions designed to simultaneously address multiple risk factors, the aim of the present study was to identify behavioral clusters including nine behaviors relating to smoking, alcohol consumption, nutrition, physical activity, and sleep.